Recall of diagnosis by men with ischaemic heart disease. - Shaper, A G (1984)
In a study of the prevalence of ischaemic heart disease in middle aged men in 24 British towns, the subjects were asked whether a doctor had ever told them that they had any form of cardiovascular disease. Their recall of various diagnoses was related to evidence of ischaemic heart disease obtained by an administered questionnaire on chest pain and electrocardiography. Twenty one per cent of men recalled a diagnosis of cardiovascular disease, in one quarter of whom it was ischaemic heart disease. There was a sixfold increase in the prevalence of recall of a diagnosis of ischaemic heart disease over the age range studied. Only one third of the men with possible myocardial infarction on questionnaire recalled such a diagnosis having been made by a doctor. Only half of those with a definite myocardial infarction on an electrocardiogram could recall a diagnosis of ischaemic heart disease. Even in severe (grade 2) angina 40% could not recall being told that they had heart disease. Overall, only one in five of those regarded as having ischaemic heart disease was able to recall such a diagnosis having been made by a doctor, and these were likely to be those most severely affected. Ischaemic heart disease is common in middle aged British men, but most of those affected are apparently not aware of their condition. This low level of awareness among patients and doctors may contribute to a lack of public concern regarding the need for action to reduce the incidence of ischaemic heart disease in Great Britain.